1993
DOI: 10.1073/pnas.90.11.4912
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of centromeric and replicative functions on autonomously replicating sequences isolated from the yeast Yarrowia lipolytica.

Abstract: Two sequences (ARS18 and ARS68) displaying autonomous replication activity were previously cloned in the yeast Yarrowia lipolytica. (4,5). The copy number ofARS plasmids in Y. lipolytica has been reported to be about 3 per plasmid-containing cell, which is also very different from the 50-100 copies for S. cerevisiae ARS plasmids (6) but closer to the 1-2 copies per cell described for centromeric plasmids (3).We wondered whether ARS18 and ARS68 are ARS sequences associated with Y. lipolytica centromeres or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 36 publications
1
61
0
1
Order By: Relevance
“…On the basis of the genetic behavior in Y. lipolytica of plasmids bearing the ARS18 and ARS68 elements, we had concluded that a centromere was present in each of these sequences (26). We decided to investigate if this was also the case for ARS2, another ARS element described for this yeast (57).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of the genetic behavior in Y. lipolytica of plasmids bearing the ARS18 and ARS68 elements, we had concluded that a centromere was present in each of these sequences (26). We decided to investigate if this was also the case for ARS2, another ARS element described for this yeast (57).…”
Section: Resultsmentioning
confidence: 99%
“…These two ARS plasmids displayed a behavior different from that of traditional ARS elements in S. cerevisiae: low copy number, higher mitotic stability, and scarcity in a genomic DNA library. These unusual properties were later attributed to the presence of a centromere within each of the two ARS elements (26). At the same time another group also described the isolation of two ARS sequences from this yeast (57).…”
Section: Although the Nature Of Higher Eukaryotic Replication Originsmentioning
confidence: 94%
See 2 more Smart Citations
“…Yet, the genetic tractability of Y. lipolytica [18][19][20][21][22][23][24] coupled with its modest, innate de novo lipogenesis (B10-15% lipid content in wild type 13,14,[25][26][27] ) make it a potential candidate as a platform organism for superior lipid production.…”
mentioning
confidence: 99%